The French of medieval England : essays in honour of Jocelyn Wogan-Browne - Fenster, Thelma S.; Collette, Carolyn P.; Wogan-Browne, Jocelyn (D.S. Brewer is an imprint of Boydell & Brewer Ltd, 2017)
Recent research has emphasised the importance of insular French in medieval English culture alongside English and Latin; for a period of some four hundred years, French (variously labelled the French of England, Anglo-Norman, Anglo-French, and Insular French) rivalled these two languages. The essays here focus on linguistic adaptation and translation in this new multilingual England, where John Gower wrote in Latin while his contemporary Chaucer could break new ground in English.